Gaps in Modern Heart Failure and Chronic Kidney Disease Research - Simran Singh Parmar; Vasantha Muthuppalaniappan; Debasish Banerjee (European Cardiology Review)
Heart failure and chronic kidney disease are common conditions and often coexist. Modern clinical trials are not entirely representative of heart failure patients in the community with respect to age and sex. Despite this, another group of heart failure patients, those with advanced chronic kidney disease, are even less represented in modern clinical trials. This review summarises the evidence for heart failure therapies across age, sex and severity of chronic kidney disease, and outlines the need for further research in these populations.